Digital transformation of the healthcare system in Serbia: attitudes of eZdravlje and HIS users - Nikola Bošković (BizInfo)
The permanent development of information technologies and the global digitization trend have transformed many sectors, including medicine. Serbia's health information system (HIS) represents a key platform for centralized data collection and processing. At the same time, its integration with the digital service eZdravlje has the potential to improve communication between health workers and patients. eZdravlje and HIS based on empirical research conducted among citizens and health workers in Serbia from February to June 2024. The results were obtained through two surveys, one of which was conducted among citizens, while the other was conducted among doctors. Based on the analysis of these data, the paper provides a comparative overview of the use of the digital services eZdravlje and HIS in Serbia. In addition, deficiencies in HIS were identified that can serve as a basis for further creation of digitization strategies, as well as improvement and improvement of health services in Serbia, in accordance with modern technological achievements.